Application of calcite-graphite carbon isotope thermometry in rehydrated high-grade metamorphic terrains: An example from Sør Rondane Mountains, East Antarctica - M., Satish-Kumar; Noriyoshi, Tsuchiya; Tetsuo, Kawakami; Masahiro, Ishikawa; Geoff, Grantham (2010)
第30回極域地学シンポジウム「極域から探る固体地球ダイナミクス」 12月2日（木） 国語研究所 ２階講堂 conference object